PENERAPAN TEXT MINING DALAM MENGANALISIS KEPRIBADIAN PENGGUNA MEDIA SOSIAL - M. Pramadani Riyanis Putra; Kiki Rizky Nova Wardani (JUTIM (Jurnal Teknik Informatika Musirawas), 2020)
Facebook”is a social networking application where users reveal a lot about the mselves”through their posting pages. So the writer wants”to know what information can be taken about the user's”personality. Data mining plays an important role”which aims to”transform raw data into a structure that can be understood”for further use. ”Text mining refers to the process of”retrieving”high quality information from text”,one of the classification methods that can be used is the K-Nearest Neighbor algorithm. Based on the theory of big five personality”the results of the study concluded that”the accuracy rate obtained was 92.92%, from 550 data with the highest openness personality character value of 239, Conscientiouseness of 16 data, Extraversion of 173 data, Agreeableness of 50 data, Neuroticism of 33 data and 39 data that cannot be classified.